Siting the New Economic Science: The Cowles Commission's Activity Analysis Conference of June 1949 - Till Düppe; E. Roy Weintraub (European Historical Economics Society (EHES), 2013)
In the decades following WWII, the Cowles Commission for Research in Economics came to represent new technical standards that informed most advances in economic theory. The public emergence of this community was manifest at a conference held in June 1949 titled Activity Analysis of Production and Allocation. Our history of this event situates the Cowles Commission among the institutions of post-war science in-between National Laboratories and the supreme discipline of Cold War academia, mathematics. Although the conference created the conditions under which economics, as a discipline, would transform itself, the participants themselves had little concern for the intellectual battles that had defined prewar university economics departments. The conference bore witness to a new intellectual culture in economic science based on shared scientific norms and techniques un-interrogated by conflicting notions of the meaning of either science or economics.
Keywords: B2; C0; 330; Cowles Commission; activity analysis; linear programming; general equilibrium theory; von Neumann; Koopmans; Dantzig; fixed point theorems